2009
DOI: 10.1108/00400910910968337
|View full text |Cite
|
Sign up to set email alerts
|

Combining study and employment: a step too far?

Abstract: PurposeThe purpose of this paper is to report the results of a survey of part‐time employment among university students. The survey seeks to establish the nature and characteristics of that employment, and to determine the extent to which it is comparable to similar institutions. The research also aims to examine the possible consequences of combining part‐time employment with full‐time study, with particular reference to stress.Design/methodology/approachThe research consisted of a web‐based survey of full‐ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 30 publications
5
46
1
Order By: Relevance
“…The majority of participants in the present study were working during their time at university, and most had gained own academic work experience during their final study year. Interestingly, this differs from previous research which suggests that students work mainly in non-academic fields (Bradley 2006;Robotham 2009;Hunt et al 2004), even if they were working during their final study year (Callender 2008). The results also confirmed previous findings that students work many hours (Callender 2008, Watts andPickering 2000).…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…The majority of participants in the present study were working during their time at university, and most had gained own academic work experience during their final study year. Interestingly, this differs from previous research which suggests that students work mainly in non-academic fields (Bradley 2006;Robotham 2009;Hunt et al 2004), even if they were working during their final study year (Callender 2008). The results also confirmed previous findings that students work many hours (Callender 2008, Watts andPickering 2000).…”
Section: Discussioncontrasting
confidence: 46%
“…The study showed more effects on study pace than on thesis grade. Thus, it might be as Robotham (2009) suggests that working has more other negative effects such as tiredness and less time for social activities than achieving lower grades only. Moreover, in most cases, work has been found to interfere more with students' leisure time, not their study time (Hovdhaugen 2013).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations